Pengaruh Penerapan Sistem Informasi Akuntansi Dan Pengendalian Internal Terhadap Kinerja Karyawan Di Kantor Notaris Is Hariyanto Imam Salwawi, S.H - Gilang Putra Ramadhan; Irwina Salsabilla; Putri Yolanda Maharani; Mohammad Mirza Pratama (CV. ITTC INDONESIA, 2024)
The purpose of this study was conducted to determine the effect of the quality of employee performance with the application of accounting information systems and Internal Control Systems in a company. the method used in this research is qualitative research. Qualitative research is a research step that produces descriptive data in the form of writing or speech, as well as the behavior of the people observed. In this study, the authors used data collection techniques, namely literature study. The literature technique is a way of collecting data obtained through literature, such as newspapers, books, magazines, manuscripts, documents, and so on that are relevant to the research. The results of the analysis of this research show that the effect of using accounting information systems and internal control is quite good because with the use of this system employees can do work effectively and quickly and reduce negligence in work. Suggestions that can be given to notary offices are expected to continue to use the internal control system in order to reduce the risk of negligence of employees.